Essential Environmental Risk Factors of Strongyloides stercoralis Infection Surrounding Tropical Rainforest East Kalimantan, Indonesia - Blego Sedionoto (Recent Updates in Disease and Health Research Vol. 8, 2024)
Aims: Strongyloides stercoralis/S. stercoralis infections are still a challenge in public health problems especially in developing countries that have Environmental risk factors. Rural areas of Kutai Kertanegara Regency have a high risk of ecological factors of the prevalence S. stercoralis infections. Study design: A cross-sectional study was performed among 213 participants from a rural community of Muarakaman District and Marangkayu Districts, Kutai Kertanegara Regency. This study would show the infection rates and correlation analysis between environmental risk factors and prevalence of hookworm infection with statistical analysis. Place and Duration of Study: We performed a cross-sectional study among 213 participants from rural community of Muarakaman District and Marangkayu Districts, Kutai Kertanegara Regency East Kalimantan Province, Indonesia. Methods: In this study used two diagnostic methods: Kato Katz and Koga agar plate culture/KAP culture for diagnosing Strongyloides stercoralis infections. Results: Pearson chi-square analysis was used to study the correlation between environmental risk factors with S. stercoralis infection. S. stercoralis infections were found in this study; 17 (8.0%). Conclusion: Environmental risk factors have a significant correlation and high odd ratio of prevalence of S. strercoralis infections. Essential environmental risk factors of the infections should be used for preventing program of reduction prevalence of S. stercoralis infections.